2017
DOI: 10.1007/s10461-017-1750-5
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the First 90: A Highly Effective Partner Notification Approach Reaches Previously Undiagnosed Sexual Partners in Tanzania

Abstract: To meet UNAIDS’ 90–90–90 treatment goals, effective approaches to HIV testing services (HTSs) are urgently needed. In 2015, a cross-sectional study was conducted to evaluate effectiveness and feasibility of partner notification for HTS in Tanzania. Men and women newly diagnosed with HIV were enrolled as index clients, listed sexual partners, and given options to notify and link their partners to HTS. Of 653 newly diagnosed individuals, 390 index clients were enrolled, listed 438 sexual partners, of whom 249 (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 14 publications
(34 reference statements)
11
57
3
Order By: Relevance
“…Stakeholders identified potential implementation challenges for each HIV testing modality. Although evaluation trials have demonstrated the effectiveness of these male partner HIV testing approaches in antenatal settings , implementation research with cost‐effectiveness analysis would be helpful to guide countries when considering partner testing approaches. While cost‐effectiveness studies in the general adult population have been promising , evidence of cost‐effectiveness in antenatal settings is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholders identified potential implementation challenges for each HIV testing modality. Although evaluation trials have demonstrated the effectiveness of these male partner HIV testing approaches in antenatal settings , implementation research with cost‐effectiveness analysis would be helpful to guide countries when considering partner testing approaches. While cost‐effectiveness studies in the general adult population have been promising , evidence of cost‐effectiveness in antenatal settings is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…These index‐based approaches can be passive, in which the index is responsible for contact recruitment, or active, in which the healthcare system supports the index with contact recruitment . Such index‐based approaches are promoted due to their potential to improve HIV testing coverage and efficiently identify other undiagnosed HIV infections .…”
Section: Introductionmentioning
confidence: 99%
“…Malawi, in its national HIV guidelines, has adopted a passive referral model , in spite of local and international evidence demonstrating the enhanced effectiveness of active approaches, along with adequate safety , acceptability and cost‐effectiveness . Active approaches have not been pursued due to concerns of cost, complexity and social harms.…”
Section: Introductionmentioning
confidence: 99%
“…Programs evaluated in published studies have varied substantially, variously relying on medical professionals and religious pastors (Cameroon), trained study staff (Kenya and Malawi), HIV testing counselors (Tanzania)[10] and community health workers (Mozambique). Some APS models have emphasized resource-intensive field investigation (Kenya and Cameroon), others have relied almost entirely on cellphone contact (Mozambique), and some have focused primarily on disclosure counseling (Tanzania).…”
mentioning
confidence: 99%